Derivation of attenuation equations for distant earthquake suitable for Malaysia - Adnan, Azlan; Meldi, Suhatril (Faculty of Civil Engineering, 2009)
One of the critical factors in seismic analysis is selecting appropriate attenuation equations. This formula, also known as ground motion relation, is a simple mathematical model that relates a ground motion parameter (i.e. spectral acceleration, velocity and displacement) to earthquake source parameter (i.e. magnitude, source to site distance, mechanism) and local site condition (Campbell, 2002). It is considered one of the critical factors in seismic hazard analysis. It may lead the design load for building either become too conservative or under design. There has been a number of attenuation equations derived in the last two decades since the record of ground motions becomes more available. In general, they are categorized according to tectonic environment (i.e. subduction zone and shallow crustal earthquakes) and site condition. There are several attenuation relationships derived for subduction zone earthquake, which are commonly used such as Crouse (1991), Youngs (1997), Atkinson and Boore (1997), Petersen (2004). Whereas attenuation relationships, which are developed by Abrahamson and Silva (1997), Campbell (1997, 2002), Sadigh et al. (1997), Toro (1997), are frequently used to estimate ground motion for shallow crustal earthquake. The shortcomings of this method are by the limitation of the attenuation relationship itself. Usually attenuation relationship is derived for near source earthquake. Therefore, most of the attenuation relationships have a distance limitation. Except attenuation developed by Toro (1997), and Campbell (2002), all of the attenuations are only valid to be applied for distances between 80 km and 400 km. Since there is no attenuation relationship has been derived directly for Malaysia region, which is affected by long distance earthquake, therefore selection or development of appropriate attenuation relationship for Malaysia is needed. This research is collaborating with related institutions such as Malaysian Meteorological Department (MMD), Jabatan Mineral dan Geosciences Malaysia (JMG) and United States Geological Survey (USGS). There are 481 recordings from 40 mainshocks and aftershocks which magnitude greater than 5.0 in the full data set. Recordings with unknown or poor estimates of the magnitude, mechanism, distance, or site condition were excluded from the data set used in the regression analysis. This reduced the data set used in the analysis to 91 recordings from 14 earthquakes.